Mathematical Models of Neural Networks: Bridging the Gap between Biology and Computation - Patel Nirmal Rajnikant; Dr. Ritu Khanna (International Journal of Scientific Research in Science and Technology, 2025)
The study of neural networks stands at a vibrant crossroads between biological insight and computational innovation. This paper explores mathematical models that faithfully capture the dynamics of biological neural systems while enabling powerful computational architectures. We examine foundational models such as the Hodgkin-Huxley and integrate-and-fire neurons, progressing to modern abstractions like spiking neural networks and deep learning frameworks. Emphasis is placed on how mathematical formalism can both illuminate biological processes and inspire new algorithms. By bridging the disciplines of neuroscience and computer science, we highlight how theoretical models not only deepen our understanding of brain function but also fuel the next generation of intelligent machines. Challenges in model fidelity, scalability, and interpretability are discussed, along with emerging approaches that promise to harmonize biological realism with computational efficiency. This synthesis of biology and computation paints a future where the brain and the machine are partners in innovation, not rivals.
Keywords: Deep Learning; Hebbian Learning; Neuromorphic Computing; Biological Neural Systems Artificial Neural Networks (ANNs); Brain-Inspired Computation; Leaky Integrate-and-Fire Model; Spiking Neural Networks (SNNs)